A 140 GHz high efficiency frequency doubler based on a physical‐based SDD model of SBD. (17th March 2021) - Yan, Bo; Ren, Tianhao; Wu, Chenkai; Wei, Haomiao; Wang, Li; Li, Yu; Xu, Ruimin; Zhang, Yong
Summary: In this paper, a physical‐based SDD (symbolically defined devices) model of SBD (Schottky barrier diode) is proposed, in which conventional C‐V characteristics of diode SPICE model are modified by terahertz C‐V characteristics obtained by physical‐based simulation. Detail modeling method and design process are introduced in detail. To verify the accuracy of the SDD model, a 140 GHz high efficiency doubler is designed, fabricated, and measured. The measured maximum efficiency is 34.3% under 90 mW input power, and the 3 dB bandwidth is about 7 GHz, which agrees well with the simulated results. The proposed physical‐based SDD model is demonstrated to be more accurate than traditional diode SPICE model. Abstract : We establish a physical‐based SDD (symbolically defined devices) model of SBD (Schottky barrier diode). The measured results of a 140 GHz doubler designed using this model agree well with the simulated results, exhibiting a higher accuracy than traditional SPICE model in Advanced Design Systems (ADS).